2016
DOI: 10.1111/and.12567
|View full text |Cite
|
Sign up to set email alerts
|

Standardised extract of safed musli (Chlorophytum borivilianum) increases aphrodisiac potential besides being safe in male Wistar rats

Abstract: The standardised extract of root of safed musli (Chlorophytum borivilianum) was evaluated for its aphrodisiac potential and safety profile on reproductive system. Wistar albino rats were trained to provide sexual experience under a dim red light (10 W) in a glass tank. Male and female rats were placed periodically in the glass tank in a particular order, that is male followed by introduction of the receptive female. Dosing of extract was carried out for 54 days at 125 and 250 mg kg p.o to male rats. On 14th an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Up to 28 days of study, sildenafil showed significant improvement in all sexual functions, that is increase in MF and IF and decrease in ML and IL as was found by Das et al. (). At 42 and 54 days of the study, a significant increase in ML and IL and a significant decrease in MF and IF of the standard/sildenafil‐treated group were observed when compared to normal control group.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Up to 28 days of study, sildenafil showed significant improvement in all sexual functions, that is increase in MF and IF and decrease in ML and IL as was found by Das et al. (). At 42 and 54 days of the study, a significant increase in ML and IL and a significant decrease in MF and IF of the standard/sildenafil‐treated group were observed when compared to normal control group.…”
Section: Discussionsupporting
confidence: 70%
“…The selection of male and female ratio for the following model is a crucial aspect. Males and females were taken in a ratio of 1:1 (Das et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations